Melihat citra perusahaan melalui big data: Polemik beasiswa perusahaan rokok - Pramana, Pinandito Dhirotsaha; Utari, Prahastiwi; Naini, Albert Muhammad Isrun (Jurnal Studi Komunikasi, 2020)
This study aimed to see the image of PT Djarum as a cigarette company during a polemic through big data approach. The public was shocked by the news that PB Djarum would terminate the Badminton scholarship that had been held for the past twelve years. It started when KPAI considered that there was an intention to exploit children using the brand of PT Djarum. Although the problem was over, the polemic had seized the public's attention. This research was an analysis of quantitative and qualitative content from Twitter social media. Quantitative analysis in the form of sentiment analysis was carried out utilising the results of 26,677 tweets data from online platforms based on big data from Drone Emprit Academic. Qualitative analysis was carried out Critical Discourse using van Dijk's model. The analysis revealed that PT Djarum has succeeded in building a positive image through its CSR program, which can be seen from the support of the majority of the Indonesian people as reflected in Twitter conversation.